Effect of nano theobromine incorporated into a primer on enamel density (An Invitro study) - Rahma A. Al-Zarq; Ali R. Al-Khatib; Ammar Abdulghani Alhamdani; Rozita Hassan (Al-Rafidain Dental Journal)
The current study aimed to evaluate the enamel density after applying an orthodontic primer containing nanotheobromine powder. Materials and methods: The sample consisted of 24 lower premolar teeth distributed into three groups (eight teeth in each group). After demineralization, the specifically prepared enamel area was covered either with a 3MTM Transbond orthodontic primer for control and with the same primer incorporated with 10% or 15% nanotheobromine powder for the experimental groups. The crowns were sectioned horizontally and longitudinally, creating 48 right and left segments. The teeth were subjected to radiological densitometry analysis in horizontal and vertical directions to evaluate the enamel density and subsequent remineralization. Results: A significant change in enamel density values was recorded in teeth covered with a primer containing 15% nano-theobromine (p>0.05), with values higher than that of the baseline (105.00±22.59, 96±23.8 grayscale). Conclusion: Both incorporating groups, particularly 15% nanotheobromin, showed an increase in enamel density and subsequent remineralization. This modified orthodontic adhesive may be useful for preventing early enamel demineralization and supporting clinicians with minimally invasive procedures.